Historical epidemiology of hepatitis C virus (HCV) in selected countries. (May 2014) - Bruggmann, P.; Berg, T.; Øvrehus, A. L. H.; Moreno, C.; Brandão Mello, C. E.; Roudot‐Thoraval, F.; Marinho, R. T.; Sherman, M.; Ryder, S. D.; Sperl, J.; Akarca, U.; Balık, İ.; et al.
Summary: Chronic infection with hepatitis C virus (HCV) is a leading indicator for liver disease. New treatment options are becoming available, and there is a need to characterize the epidemiology and disease burden of HCV. Data for prevalence, viremia, genotype, diagnosis and treatment were obtained through literature searches and expert consensus for 16 countries. For some countries, data from centralized registries were used to estimate diagnosis and treatment rates. Data for the number of liver transplants and the proportion attributable to HCV were obtained from centralized databases. Viremic prevalence estimates varied widely between countries, ranging from 0.3% in Austria, England and Germany to 8.5% in Egypt. The largest viremic populations were in Egypt, with 6 358 000 cases in 2008 and Brazil with 2 106 000 cases in 2007. The age distribution of cases differed between countries. In most countries, prevalence rates were higher among males, reflecting higher rates of injection drug use. Diagnosis, treatment and transplant levels also differed considerably between countries. Reliable estimates characterizing HCV‐infected populations are critical for addressing HCV‐related morbidity and mortality. There is a need to quantify the burden of chronic HCV infection at the national level.